Vector surveillance and eradication in primary health care - Ada Crespo Guzmán; Luisa Domínguez Guerrero; Adriana Méndez Castellano; Yanet Alfonso Garlobo (Medwave, 2011)
A bibliographical revision was done about in Dengue fever and the control that is carrier on against the Aedes aegypti “mosquito”, the principal agent that treatments this illness, with the objective of describing the functioning of the Control and Elimination Program of the Mosquito in the Cuban Primary Health Care System. The main objective of this program is to avoid the Dengue epidemics and the loss of human life and the negative impact that will cost to, the socioeconomic development of over country. Accomplishing the promotion, prevention and controlling actions by the basic health care team the mosquito campaign workers and our population, the vector infestation index has been diminished below 0.5 in the last five years. It is important to point out that the rapid decisions taken by our government and its consequent efforts and political willingness has made this program sustained.